Mechanical properties and fibre density of steel fibrereinforced self-compacting concrete slabs by DIA and XCT approaches - Ponikiewski, Tomasz; Katzer, Jacek (Journal of Civil Engineering and Management, 2017)
The aim of the research programme was to investigate flexural behaviour of steel fibre reinforced self-compacting concrete (SFRSCC). The specimens were in a form of slabs reinforced with steel fibres (of three lengths and two shapes) by volumes of 1.0% and 1.5%. Two methods of casting slabs were examined. The experimental tests performed on 80 specimens cut from slabs (1.2×1.2×0.15 m) involved tests of mechanical properties, digital image analysis (DIA), and X-ray computed tomography (XCT) procedures. Determination of distribution of fibres by DIA and XCT was required to assess relationships between mechanical properties and the casting methods. The tests were conducted according to RILEM TC 162-TDF (2002) and EN 14651:2005+A1:2007(E) recommendations. The study confirmed the technological problems associated with uneven distribution of steel fibres in SCC matrix. Based on the performed analysis, the flexural tensile strength of SFRSCC cannot be described with the formulas used for SFRC. Fibres are generally oriented parallel to the direction of concrete mixture flow in a mould. This phenomenon is influenced by fibre length and the location of concrete casting point (CCP). It was also demonstrated that the flexural behaviour of tested elements is influenced by CCP.